The Driving Forces of Change in Energy-related CO2 Emissions in the Polish Iron and Steel Industry in 1990-2017 - GoÅ‚aÅ›, Zbigniew (International Journal of Energy Economics and Policy, 2020)
The main purpose of this paper was to identify the driving forces of change in energy-related CO2 emissions in the Polish iron and steel industry in 1990–2017. The analysis relied on the LMDI method used for both the entire study period and the seven 3-year sub-periods. Changes in energy-related CO2 emissions were considered in the context of four factors: the effect of the emission factor; the effect of the energy mix; the effect of energy consumption; and the effect of the production volume of steel. As shown by these analyses, CO2 emissions in the Polish iron and steel industry dropped by as much as over 60% during the study period. That process was primarily driven by a reduction in steel production volumes and in energy intensity of production. In 1990–2017, these factors contributed 48.0% and 50.7%, respectively, to total change in CO2 emissions. Other factors, i.e. emission intensity and energy mix, had a marginal impact. However, the opportunities for further reduction in CO2 emissions seem very limited in the Polish iron and steel industry. That sector is unable to incur the costs of decarbonization investments and requires financial support. Moreover, its continued existence depends on changes to the ETS which will promote low-emission production and will stop the shrinking of the steel market. Thirdly, the steel market needs to be protected against unfair imports, and requires the establishment of the same competition conditions for producers who are not charged with CO2 emission costs. Keywords: CO2 emission, energy use, LMDI decomposition, iron and steel industry, Poland JEL Classifications: Q42, Q43, Q53 DOI: https://doi.org/10.32479/ijeep.9444